Development of a Community-engaged Research Training Workshop for Clinician-Scientists and Early-stage Investigators - Emily P. Courtney; Cathy D. Meade; Clement K. Gwede; Veronica Barrios-Monroy; Isabel C. Scarinci; Usha Menon; Monica Baskin; David Schwartz; Monica E. Peek; Anissa I. Vines; Z’Kera Peoples; Jamboor K Vishwanatha; et al. (Journal of Cancer Education, 2026)
Community-engaged research (CEnR), a collaboration between academics and community partners, is an effective approach in addressing the social drivers of health (SDOH) and health disparities in local communities. Yet, CEnR training is often not a standard component of training programs in research or clinical programs. To meet the need for CEnR training, we developed and implemented a workshop to increase CEnR knowledge and skills among clinician-scientists and early-stage investigators (ESIs), and create opportunities for ongoing mentorship and professional development. In this manuscript, we discuss the organization of this workshop, learning objectives, supporting activities, and follow-up methods to facilitate a successful and engaging training experience. The workshop was developed through collaborative efforts with experts in CEnR, Community-Based Participatory Research (CBPR), cancer disparities, and SDOH. The workshop focused on (1) an introduction to CEnR and the opportunity for attendees to develop their own CEnR research ideas; (2) varied presentations, interactive activities, experiential learning, and discussion topics to fulfill the workshop’s learning objectives; (3) year-long opportunities for professional development and continued mentorship; and (4) evaluations of the workshop. Twenty-four ESIs and 11 clinician-scientists participated in the workshop. Using survey methods and descriptive statistics, the workshop was evaluated positively by participants. This manuscript provides guidance for both in-person and virtual workshop formats, from inception to implementation, and recommendations for other workshop facilitators. The impact of these workshops has the potential to have positive downstream implications for community-engaged research.

Empathy in Adults with Acquired Brain Injury: a Systematic Review and Meta-Analysis - Emily Clements; Kristin Naragon-Gainey; Michael Weinborn; Carmela Pestell; Dawn Neumann; David Preece; Rodrigo Becerra (Neuropsychology Review, 2026)
Empathy is the ability to recognise, share and understand others’ emotional states. Increasing evidence suggests that empathy may be impacted by acquired brain injury (ABI), with consequences for social and emotional functioning. However, the literature has been characterised by inconsistent findings and small sample sizes. To address these limitations, we provide the first meta-analytic review of empathy in adults with ABI. Specifically, the review aimed to quantify the degree of impairment in adults with ABI across four empathy-related domains: cognitive, affective, empathic concern (e.g. sympathy) and personal distress. We also sought to estimate the prevalence of deficits in each area and explore whether demographic and injury factors moderate impairment. A systematic search yielded 29 studies measuring self-reported empathy in adults with ABI versus healthy, matched peers. A series of random-effects meta-analyses revealed moderate deficits in cognitive empathy (Hedges’ g = − 0.68, 95% CI [− 0.87, − 0.50]) and affective empathy (Hedges’ g = − 0.43, 95% CI [− 0.65, − 0.21]), as well as small-to-moderate deficits in empathic concern (Hedges’ g = − 0.38, 95% CI [− 0.63, − 0.13]). No significant difference was found for personal distress. We estimated the proportion of ABI participants scoring equal to or more than 1 SD below the normative mean to be 15.3–35.0%, depending on the empathy subcomponent. Our results highlight that empathy deficits may play an important role in functional or emotional difficulties post-brain injury. This demonstrates the need for routine clinical assessment of empathy in survivors of brain injury and the need to develop interventions which target both cognitive and affective components.

Impact of drought on de facto reuse and water quality in Lake Mead: Insights from hydrodynamic modeling versus machine learning - Charlotte van der Nagel; Emily Clements; Carissa Wilkerson; Deena Hannoun; Todd Tietjen (Environmental Modelling & Software, 2025)

Risk of gastrointestinal illness due to Campylobacter exposure in urban waterways for unsheltered persons experiencing homelessness - Katherine C Crank; Emily Clements; Casey Barber; Katerina Papp; Daniel Gerrity (Water Research, 2025)

Correction to: Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2025)

Using Community Composition and Successional Theory to Guide Site‐Specific Coral Reef Management - Orion S. McCarthy; Emily L. A. Kelly; Anela K. Akiona; Samantha M. Clements; Tatiana Martinez; Nicole E. Pedersen; Cole Peralto; Sarah L. Romero; Mitchell H. Smelser; Kristy Wong Stone; Russell T. Sparks; Jennifer E. Smith (Global Change Biology, 2025)
High spatial or temporal variability in community composition makes it challenging for natural resource managers to predict ecosystem trajectories at scales relevant to management. This is commonly the case in nearshore marine environments, where the frequency and intensity of disturbance events vary at the sub‐kilometer to meter scale, creating a patchwork of successional stages within a single ecosystem. The successional stage of a community impacts its stability, recovery potential, and trajectory over time in predictable ways. Here we demonstrate the value of successional theory for interpreting fine‐scale community heterogeneity using Hawaiian coral reefs as a case study. We tracked benthic community dynamics on 36 forereefs over a 6‐year period (2017–2023) that captures impacts from high surf events, a marine heatwave, and unprecedented shifts in human behavior due to the COVID‐19 pandemic. We document high spatial variation in benthic community composition that was only partially explained by island and environmental regime. Through hierarchical clustering, we identify three distinct community types that appear to represent different successional stages of reef development. Reefs belonging to the same community type exhibited similar rates of change in coral cover and structural complexity over time, more so than reefs located on the same island. Importantly, communities that were indicative of early succession (low coral cover reefs dominated by stress‐tolerant corals) were most likely to experience an increase in coral cover over time, while later‐stage successional communities were more likely to experience coral decline. Our findings highlight the influence of life history and successional stage on community trajectories. Accounting for these factors, not simply overall coral cover, is essential for designing effective management interventions. Site‐specific management that accounts for a community's unique composition and history of disturbance is needed to effectively conserve these important ecosystems.

Classification machine learning to detect de facto reuse and cyanobacteria at a drinking water intake - Emily Clements; Kyle A. Thompson; Deena Hannoun; Eric R.V. Dickenson (Science of The Total Environment, 2024)

Effects of temperature on nitrifying membrane-aerated biofilms: An experimental and modeling study - Emily Clements; Yanina Nahum; Patricia Pérez-Calleja; Bumkyu Kim; Robert Nerenberg (Water Research, 2024)

Acute effects of high-intensity exercise on brain mechanical properties and cognitive function - Grace McIlvain; Emily M. Magoon; Rebecca G. Clements; Alexis Merritt; Lucy V. Hiscox; Hillary Schwarb; Curtis L. Johnson (Brain Imaging and Behavior, 2024)
Previous studies have shown that engagement in even a single session of exercise can improve cognitive performance in the short term. However, the underlying physiological mechanisms contributing to this effect are still being studied. Recently, with improvements to advanced quantitative neuroimaging techniques, brain tissue mechanical properties can be sensitively and noninvasively measured with magnetic resonance elastography (MRE) and regional brain mechanical properties have been shown to reflect individual cognitive performance. Here we assess brain mechanical properties before and immediately after engagement in a high-intensity interval training (HIIT) regimen, as well as one-hour post-exercise. We find that immediately after exercise, subjects in the HIIT group had an average global brain stiffness decrease of 4.2% ( p < 0.001), and an average brain damping ratio increase of 3.1% ( p = 0.002). In contrast, control participants who did not engage in exercise showed no significant change over time in either stiffness or damping ratio. Changes in brain mechanical properties with exercise appeared to be regionally dependent, with the hippocampus decreasing in stiffness by 10.4%. We also found that one-hour after exercise, brain mechanical properties returned to initial baseline values. The magnitude of changes to brain mechanical properties also correlated with improvements in reaction time on executive control tasks (Eriksen Flanker and Stroop) with exercise. Understanding the neural changes that arise in response to exercise may inform potential mechanisms behind improvements to cognitive performance with acute exercise.

Perceived constraints to participating in wildlife-related recreation - Nicholas W. Cole; Emily J. Wilkins; Kaylin R. Clements; Rudy M. Schuster; Ashley A. Dayer; H.W. Harshaw; David C. Fulton; Jennifer N. Duberstein; Andrew H. Raedeke (Journal of Outdoor Recreation and Tourism, 2024)

Impact of fixture purging on water age and excess water usage, considering stochastic water demands - Emily Clements; Christopher Irwin; Alexandros Taflanidis; Kyle Bibby; Robert Nerenberg (Water Research, 2023)

Neotropical Anacardiaceae (cashew family) - John D. Mitchell; Susan K. Pell; Julien B. Bachelier; Emily J. Warschefsky; Elizabeth M. Joyce; Laura Calvillo Canadell; Cíntia Luíza da Silva-Luz; Clement Coiffard (Brazilian Journal of Botany, 2022)
Anacardiaceae is an ecologically and economically important plant family of about 200 species in 32 genera in the Neotropics. The family is particularly diverse in leaf architecture and fruit morphology, making it a model family to study the evolution of structural diversity as it correlates with lineage diversification. This fruit diversity is the primary reason 11 of the Neotropical genera are monotypic and that so many genera are recognized in the Anacardiaceae. The economic value of the family is driven by the global markets for cashews, mangoes, and pistachios, but there is great potential value in its medicinal properties. At least 10 Neotropical genera cause contact dermatitis, which is a rich area for research in the family. Here presented is a review of the systematics and structural diversity of the family. Particular attention is given to the morphology, economic botany, paleobotany, ecology, and taxonomy of native and naturalized genera. Keys to Neotropical Anacardiaceae subfamilies and genera are provided along with descriptions of native genera.

Assessing the conservation risk of Sphaerodactylus notatus, the U.S. herpetofaunal species most vulnerable to sea level rise - Stephanie L. Clements; Emily A. Powell; Caitlin C. Mothes; Christopher A. Searcy (Biodiversity and Conservation, 2021)

Paternally‐biased gene expression follows kin‐selected predictions in female honey bee embryos - Nicholas M. A. Smith; Boris Yagound; Emily J. Remnant; Charles S. P. Foster; Gabriele Buchmann; Michael H. Allsopp; Clement F. Kent; Amro Zayed; Stephen A. Rose; Kitty Lo; Alyson Ashe; Brock A. Harpur; et al. (Molecular Ecology, 2020)
The Kinship Theory of Genomic Imprinting (KTGI) posits that, in species where females mate with multiple males, there is selection for a male to enhance the reproductive success of his offspring at the expense of other males and his mating partner. Reciprocal crosses between honey bee subspecies show parent‐of‐origin effects for reproductive traits, suggesting that males modify the expression of genes related to female function in their female offspring. This effect is likely to be greater in the Cape honey bee ( Apis mellifera capensis ), because a male's daughters have the unique ability to produce female offspring that can develop into reproductive workers or the next queen without mating. We generated reciprocal crosses between Capensis and another subspecies and used RNA‐seq to identify transcripts that are over‐ or underexpressed in the embryos, depending on the parental origin of the gene. As predicted, 21 genes showed expression bias towards the Capensis father's allele in colonies with a Capensis father, with no such bias in the reciprocal cross. A further six genes showed a consistent bias towards expression of the father's allele across all eight colonies examined, regardless of the direction of the cross. Consistent with predictions of the KTGI, six of the 21 genes are associated with female reproduction. No gene consistently showed overexpression of the maternal allele .

Responses of soil extracellular enzyme activities to experimental warming and CO2 enrichment at the alpine treeline - Rômulo C. Souza; Emily F. Solly; Melissa A. Dawes; Frank Graf; Frank Hagedorn; Simon Egli; Charles R. Clement; Laszlo Nagy; Christian Rixen; Martina Peter (Plant and Soil, 2017)

Investigating functional redundancy versus complementarity in Hawaiian herbivorous coral reef fishes - Emily L. A. Kelly; Yoan Eynaud; Samantha M. Clements; Molly Gleason; Russell T. Sparks; Ivor D. Williams; Jennifer E. Smith (Oecologia, 2016)

What a difference a bay makes: natural variation in dietary resources mediates growth in a recently settled herbivorous fish - Mark A. Priest; Andrew R. Halford; Kendall D. Clements; Emily Douglas; Sheena L. Abellana; Jennifer L. McIlwain (Coral Reefs, 2016)

Impact of Fluid–Structure Interaction on Direct Tumor-Targeting in a Representative Hepatic Artery System - Emily M. Childress; Clement Kleinstreuer (Annals of Biomedical Engineering, 2014)

Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2014)
HIV-associated neurocognitive disorder (HAND), characterized by a wide spectrum of behavioral, cognitive, and motor dysfunctions, continues to affect approximately 50 % of HIV(+) patients despite the success of combination antiretroviral drug therapy (cART) in the periphery. Of note, potential toxicity of antiretroviral drugs in the central nervous system (CNS) remains remarkably underexplored and may contribute to the persistence of HAND in the cART era. Previous studies have shown antiretrovirals (ARVs) to be neurotoxic in the peripheral nervous system in vivo and in peripheral neurons in vitro. Alterations in lipid and protein metabolism, mitochondrial damage, and oxidative stress all play a role in peripheral ARV neurotoxicity. We hypothesized that ARVs also induce cellular stresses in the CNS, ultimately leading to neuronal damage and contributing to the changing clinical and pathological picture seen in HIV-positive patients in the cART era. In this report, we show that ARVs are neurotoxic in the CNS in both pigtail macaques and rats in vivo. Furthermore, in vitro, ARVs lead to accumulation of reactive oxygen species (ROS), and ultimately induction of neuronal damage and death. Whereas ARVs alone caused some activation of the endogenous antioxidant response in vitro, augmentation of this response by a fumaric acid ester, monomethyl fumarate (MMF), blocked ARV-induced ROS generation, and neuronal damage/death. These findings implicate oxidative stress as a contributor to the underlying mechanisms of ARV-induced neurotoxicity and will provide an access point for adjunctive therapies to complement ARV therapy and reduce neurotoxicity in this patient population.

Computer Modeling of Controlled Microsphere Release and Targeting in a Representative Hepatic Artery System - Christopher A. Basciano; Clement Kleinstreuer; Andrew S. Kennedy; William A. Dezarn; Emily Childress (Annals of Biomedical Engineering, 2010)